The study of histological changes of the arterial vascular structure after hyaluronidase exposure - Penpun Wattanakrai (2019)
© 2018 Wiley Periodicals, Inc. Background: Hyaluronic acid (HA) filler injection is commonly used for soft tissue augmentation. Uncommon but serious complication from filler injection is vascular occlusion. Hyaluronidase enzyme can be used to dissolve HA filler. Evidence demonstrates that hyaluronidase can penetrate through vessel wall after incubation. However, studies regarding effects of hyaluronidase on vessel wall after intraluminal injection are limited. The objective of this study is to evaluate histological changes of postmortem arteries after intravascular injection of hyaluronidase enzyme. Methods: This was an ex vivo experiment including arterial specimens from four cadavers which recently deceased within 24 hours. All vessels were examined at baseline and then were divided into two groups. The first was the control group treated with normal saline and the second hyaluronidase-treated group was intra-luminally injected with hyaluronidase enzyme (1500 IU/mL). Gross and histological examination was performed at baseline, 30-minutes and 4 hours after. Results: Gross examination of vessels revealed no significant difference at baseline, 30 minutes and 4 hours after injection in both groups. Histological examinations at baseline and 30 minutes after injection revealed viable endothelial cells in both experimental and NSS-control group. At 4 hours after hyaluronidase injection, two of the four arterial specimens had degeneration of endothelial cell, and one artery showed separation of tunica intima from tunica media. Conclusion: There were endothelial injuries in the arterial specimens after intravascular concentrated hyaluronidase injection.